Sturge-Weber Syndrome - Chen, Ling (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Sturge-Weber syndrome (SWS) is a neurocutaneous syndrome, characterized by the association of facial port-wine hemangiomas in the trigeminal nerve distribution area, with vascular malformation(s) of the brain (leptomeningeal angioma) with or without glaucoma. Herein, we reported Sturge-Weber syndrome in a 50-year-old man, who presented port-wine hemangiomas and epilepsy. In this case, the patient's epilepsy episodes from his first year of life had been ignored and separated from the entity of SWS by his physicians, which led to delayed treatment. This case illustrates the importance of careful examination of patients of any age with hemangiomas in the trigeminal nerve with concomitant episodes of epilepsy. In such cases, there should be yearly neuroimaging screenings to guaranteed early interdisciplinary interventions from the time of definite diagnosis.